(untitled) (Acta Entomologica Serbica, 2020)
Three species of grass moths (Crambidae) were recorded for the first time in the country. Udea alpinalis and Crambus ericella were recorded on the peaks Guslica and Snježnik in Gorski kotar region, while Catoptria pyramidellus was recorded on several different mountain chains across the country. The record of three montane species in Croatia shows the lack of Microlepidoptera surveys and the need for further visits to those areas.